THE ROLE OF NOTARIES IN PREVENTING TAX AVOIDANCE IN THE SALE AND PURCHASE OF NON-LAND ASSETS BETWEEN PARTIES IN RELATIONSHIPS - Prisilia Permata Putri; Edy Gunawan (Judge : Jurnal Hukum, 2025)
This study examines the strategic role of notaries in preventing tax avoidance practices in non-land asset sale and purchase transactions between parties with special relationships. Using a normative legal research method through a conceptual and legislative approach, this study analyzes how the notary's understanding and prudence can prevent the use of deeds as a means of tax avoidance, particularly in determining transaction prices. Notaries, as public officials authorized to draw up authentic deeds, have an important role in ensuring that transactions are legally valid, reasonable, and in accordance with tax regulations. The application of the Know Your Customer (KYC) principle and the arm's length principle (ALP), as stipulated in Minister of Finance Regulation No. 172 of 2023, is crucial for notaries to assess indications of special relationships and record transaction values accurately and objectively. Thus, notaries can contribute to creating transparency and tax compliance.